Design Strategies and Guide lines for Tropical Coast of Pakistan, Using Climate Consultant - Khalid, Asma (European Journal of Sustainable Development, 2016)
The performance and design of climate responsive buildings requires a detailed study of different attributes of climate. Climate Consultant proposes different design strategies suitable for a particular climate using a characteristic analysis. The variety of analysing climatic parameters for a particular location is facilitated with the help of available human thermal comfort models (HTCMs). This paper gives a comparative analysis for the application of various HTCMs using a weather profile of Karachi city in Pakistan. The software results are analysed using an EPW (Energy plus weather) data file from online data base of US Department of Energy. The software lists 20 guide lines based on the design strategies and criteria defined earlier for each model. Their comparative analysis helps in outlining commonalities in effective design methods. The architectural orientation, natural ventilation and the envelope materials were found to be the most workable approaches for hot humid climate of Karachi. Keyword: Climate Consultant, Human thermal comfort model, climate responsive design, architectural orientation, natural ventilation, envelope materials